2005
DOI: 10.2174/0929867053363478
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosal Protection: From Prostaglandins to Gene-Therapy

Abstract: The maintenance of gastric mucosal function and integrity highly depends on the status of microcirculation. Vasoactive agents--prostaglandins, nitric oxide and sensory neuropeptides (e.g. calcitonin gene-related peptide)--play a crucial role in mucosal defensive processes. Beside the local release of vasoactive mediators the central nervous system is also involved in regulation of gastric functions. Cerebral lesions, stimulation of different brain areas can result in gastric mucosal injury. Noxious challenge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 204 publications
(298 reference statements)
0
38
0
2
Order By: Relevance
“…The dorsal vagal complex is likely to have a prominent role in conveying the centrally initiated effect to the periphery. It was shown that both vagotomy and atropine decreased the gastroprotective effects of centrally injected thyrotropin releasing hormone (TRH), adrenomedullin, peptide YY, opioid peptides, clonidine (for reviews see Gyires, 2005;Tache 2012), nociceptin, nocistatin and cannabinoids (Shujaa et al, 2009;Zádori et al, 2008). Pharmacological and biochemical studies have shown that activation of vagal cholinergic pathways stimulates gastric prostaglandin and NO release and the "efferent function" of capsaicin sensitive primary afferent fibers containing CGRP (Kato et al, 1994;Saperas et al, 1995;Yoneda and Tache, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal vagal complex is likely to have a prominent role in conveying the centrally initiated effect to the periphery. It was shown that both vagotomy and atropine decreased the gastroprotective effects of centrally injected thyrotropin releasing hormone (TRH), adrenomedullin, peptide YY, opioid peptides, clonidine (for reviews see Gyires, 2005;Tache 2012), nociceptin, nocistatin and cannabinoids (Shujaa et al, 2009;Zádori et al, 2008). Pharmacological and biochemical studies have shown that activation of vagal cholinergic pathways stimulates gastric prostaglandin and NO release and the "efferent function" of capsaicin sensitive primary afferent fibers containing CGRP (Kato et al, 1994;Saperas et al, 1995;Yoneda and Tache, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…7) Physiological factors of these gastric diseases include acid-pepsin secretion, parietal cell activity, mucosal barrier, mucus secretion, blood ‰ow, cell regeneration, and the release of endogenous protective agents, especially prostaglandins and epidermal growth factors. 8) One of the greatest concerns is to ascertain whether H. pylori-induced gastritis may lead to gastric cancer. According to several epidemiologic studies concerning the association between gastric cancer and H. pylori, the antibodies for H. pylori was increased and higher in the patients with gastric cancer than in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors contribute to and amplify the damaging effect of acetic acid on the glandular cells. Besides, nitric oxide (NO) plays a role also in ulcer healing by stimulating the formation of growth factors, the epithelial proliferation and angiogenesis (Gyires, 2005). It was observed that AEP enhanced the NOx levels (Freitas et al, 2004) and then increased the blood flow and stimulated some events for the mucosal regeneration.…”
Section: Resultsmentioning
confidence: 99%